Pyloric Atresia- A Case Report - Hanif, A; Hasina, K; Hassan, K; Hasanuzzaman, ASM; Islam, N; Hossain, AZ; Talukder, MQ-K (Bangladesh Journal of Child Health, 2010)
Infantile hypertrophic pyloric stenosis (IHPS) is a common cause of gastric outlet obstruction in infant. The prevalence of IHPS ranges from 1.5 to 4.0 in 1000 live birth. But the incidence of IHPS has been increasing approximately from 1.5 to 4.0 in 1000 live birth to 1:150. Though pyloric atresia is a very uncommon cause of gastric outlet obstruction in infant but atresia in this region occurs in the form of web, membrane/diaphragm or rarely solid cord. Membrane/ diaphragm may be single or double and may be perforated or imperforated. If the size of perforation is less than 10 mm, it causes complete obstruction. We report the presentation and management of such a child. DOI: 10.3329/bjch.v33i1.5674 Bangladesh Journal of Child Health 2009; Vol.33(1): 35-36